SENSORIAL NARRATIVES OF MEMORY AS THE BASIS OF URBAN ARCHITECTURE - Samuel Hendra Saputra; Gaby Fitria Bahri; Kristanti Dewi Paramita; Paramita Atmodiwirjo (MODUL, 2026)
This design study explores memory narratives of space and how it provides sensorial experience as the basis of urban architecture. Discussion about architecture focuses on its permanent presence as long-lasting structures that can withstand forces of time. This study instead explores the fleeting interplay between time, memory, and senses embedded in the city narratives. This study employed a memory walk within the Gading Serpong area in Tangerang, Banten, Indonesia, to gather spatial memories and sensorial experiences of such an area as an ever-evolving urban area. The narratives acquired from this urban walk are encoded to address how it is comprised of multiple experiences of the senses. The narratives are then used to generate spatial propositions of the Mnemonic City initiative, a speculative form of urban architecture encompassing structures blazing with intricate memories. The Mnemonic City initiative is assembled as trajectories of sensorial narratives, using memory as the basis of the mechanism. Such mechanisms enable developments of spatiality that accommodate the next generation to have a strong connection with the entire city, celebrating the fleeting but lasting existence of memories in the temporality of space.